Local Wisdom of Kerja Rani: A Study of Traditional Values and Human Ecology in the Batak Karo Protestant Church in Facing the Modern Ecological Crisis - Brema , Andi; Harahap, Rahma Hayati; Saputra, Dony (TALENTA Publisher, 2025)
Kerja Rani is a harvest thanksgiving tradition in the Batak Karo Protestant Protestan (GBKP), reflecting the relationship between the congregation and nature. Although rooted in the agrarian culture of the Karo people, the practice has changed, especially among urban congregations. This research aims to identify ecological values in Kerja Rani and its relevance in the context of the current environmental crisis. Through a literature study, findings show that Kerja Rani can serve as a means to raise ecological awareness and strengthen human relationships with nature. GBKP has the opportunity to utilize this ritual in environmental education, inviting congregants to appreciate the role of nature and integrate sustainability values in daily life.